2023
DOI: 10.1002/ab.22113
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes of physical, sexual, and psychological intimate partner violence among women in Turkey: A latent class study

Cennet Yastıbaş‐Kaçar,
Mete S. Uysal,
Duygu Güngör

Abstract: Intimate partner violence (IPV) is a severe human right violation and a significant public health problem in Turkey. However, its complexity and stratified relationship with mental health problems are still uncovered in this under researched community, as violence is often approached as a uniform health and social problem. In this study, we collected data from 539 female adults in heterosexual relationships in Turkey using convenience and snowball sampling. The aim was to examine violence‐related clusters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…Moreover, a more recent study revealed that vertical collectivism, referring to being more supportive of patriarchy and gender differentiation, which, in turn, led to greater acceptance of IPV myths, thus violence might be perceived as less abusive in Turkey . However, our study provided strong evidence that psychological IPV has detrimental effects on psychological well-being, in line with a recent research in Turkey (Yastıbaş-Kaçar et al, 2023) and a similar cultural context (Wong et al, 2011), as well as previous research (Costa & Gomes, 2018;Ludermir et al, 2010). It is obvious that even if the honor concept varies in different cultures, women may be justified in accepting psychological IPV in their relationship, it may harm their psychological well-being.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a more recent study revealed that vertical collectivism, referring to being more supportive of patriarchy and gender differentiation, which, in turn, led to greater acceptance of IPV myths, thus violence might be perceived as less abusive in Turkey . However, our study provided strong evidence that psychological IPV has detrimental effects on psychological well-being, in line with a recent research in Turkey (Yastıbaş-Kaçar et al, 2023) and a similar cultural context (Wong et al, 2011), as well as previous research (Costa & Gomes, 2018;Ludermir et al, 2010). It is obvious that even if the honor concept varies in different cultures, women may be justified in accepting psychological IPV in their relationship, it may harm their psychological well-being.…”
Section: Discussionsupporting
confidence: 90%